PERILAKU KECANDUAN MENONTON DRAMA KOREA DAN NILAI KARAKTER SISWA SMK LABOR BINAAN FKIP UNRI PEKANBARU - Yanti Permata Sari; Rosmawati Rosmawati; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Behavior addiction watching Korean drama is an overreaction that arises from one's self towards Korean art. The phenomenon that occurs among students is the students who use the Korean language during the learning process, during the spare time students use to watch Korean drama, some students invite teachers to use Korean language and students collect accessories related to korea. The purpose of this research is to know the description of behavior of student addiction level about drama korea and to know picture of student character value. This research uses quantitative method with descriptive approach. The sample in this study were 105 students of class X and class XI consisting of male and female students. The results of this study indicate that the addiction to watching Korean dramas is at the low category level (71%). Someone said to be addicted to watching Korean dramas can be seen in the behavior of salience, mood modification, conflict, tolerance, withdrawal symptoms, and relapse. The student character score in this study was at the good category level (77%). A person can be said to be very good in honesty, discipline, courtesy, responsibility, cooperation, confidence, creativityKey Words: Behavior, Addiction, Character Value